FROM RECOVERY TO AESTHETICS: A CASE OF INTERNAL BLEACHING ASSOCIATED WITH COMPOSITE RESIN VENEER. - Nogueira, Graciane Santos; Leal, Sabrina de Oliveira; da Mata da Costa, Leandro; Damasceno, Janaina Emanuela (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: Aesthetic dental enhancement has become increasingly relevant, gaining prominence and importance, with symmetry, shape, contour, and especially color playing a crucial role. In this context, chromatic alteration of the teeth, resulting from numerous factors, is one of the main reasons for dissatisfaction with the aesthetics and harmony of the smile, leading to methodologies that seek to restore dental naturalness in a conservative manner. Aim: This study aims to highlight, through a clinical case of a young patient, the aesthetic rehabilitation of a post-trauma upper lateral incisor, through endodontic treatment, followed by dental whitening and direct composite resin veneer. Case report: Conservative treatment through endodontics of the tooth, internal whitening with 20% sodium perborate, in-office whitening with 35% hydrogen peroxide, and after 7 days of stabilization, composite resin veneer for dental harmony. Discussion: The success of the treatment depends on the choice of material, accurate diagnosis, and proper execution of the technique. Conclusion: Conservative techniques are considered promising approaches for maintaining dental structure without the need for tooth structure removal to restore the aesthetic appearance of tooth darkening post-trauma.